Transcriptome analysis of Haloquadratum walsbyi: vanity is but the surface - Henk Bolhuis (BMC Genomics, 2017)
Abstract Background Haloquadratum walsbyi dominates saturated thalassic lakes worldwide where they can constitute up to 80-90% of the total prokaryotic community. Despite the abundance of the enigmatic square-flattened cells, only 7 isolates are currently known with 2 genomes fully sequenced and annotated due to difficulties to grow them under laboratory conditions. We have performed a transcriptomic analysis of one of these isolates, the Spanish strain HBSQ001 in order to investigate gene transcription under light and dark conditions. Results Despite a potential advantage for light as additional source of energy, no significant differences were found between light and dark expressed genes. Constitutive high gene expression was observed in genes encoding surface glycoproteins, light mediated proton pumping by bacteriorhodopsin, several nutrient uptake systems, buoyancy and storage of excess carbon. Two low expressed regions of the genome were characterized by a lower codon adaptation index, low GC content and high incidence of hypothetical genes. Conclusions Under the extant cultivation conditions, the square hyperhalophile devoted most of its transcriptome towards processes maintaining cell integrity and exploiting solar energy. Surface glycoproteins are essential for maintaining the large surface to volume ratio that facilitates light and organic nutrient harvesting whereas constitutive expression of bacteriorhodopsin warrants an immediate source of energy when light becomes available.